2023
DOI: 10.3390/rs15041090
|View full text |Cite
|
Sign up to set email alerts
|

Integrating UAV-Derived Information and WorldView-3 Imagery for Mapping Wetland Plants in the Old Woman Creek Estuary, USA

Abstract: The classification of wetland plants using unmanned aerial vehicle (UAV) and satellite synergies has received increasing attention in recent years. In this study, UAV-derived training and validation data and WorldView-3 satellite imagery are integrated in the classification of five dominant wetland plants in the Old Woman Creek (OWC) estuary, USA. Several classifiers are explored: (1) pixel-based methods: maximum likelihood (ML), support vector machine (SVM), and neural network (NN), and (2) object-based metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In the study, the use of UAV allowed us to collect more information on mangroves on a larger scale, and the use of UAV imagery allowed for the precise selection of training and validation samples of satellite imagery, thereby increasing the accuracy of satellite-image classification, while minimizing or eliminating the interference of field surveys in mangrove ecosystems [65]. Islam et al [40] corroborated that UAV-derived information was effective in mapping wet vegetation. Research by Oldeland et al has shown that UAV can greatly assist field surveys for plant-species monitoring by providing accurate species maps as well [66].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the study, the use of UAV allowed us to collect more information on mangroves on a larger scale, and the use of UAV imagery allowed for the precise selection of training and validation samples of satellite imagery, thereby increasing the accuracy of satellite-image classification, while minimizing or eliminating the interference of field surveys in mangrove ecosystems [65]. Islam et al [40] corroborated that UAV-derived information was effective in mapping wet vegetation. Research by Oldeland et al has shown that UAV can greatly assist field surveys for plant-species monitoring by providing accurate species maps as well [66].…”
Section: Discussionmentioning
confidence: 90%
“…The findings demonstrated a significant improvement in classification accuracy due to the incorporation of texture features. This improvement was attributed to the inherent variation among the different species within the mangrove ecosystem, which included a variety of leaf shapes, average heights, and branch structures [40]. In high-resolution remotely sensed imagery, these distinct attributes appear as texture features [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they occupy a small portion of the earth but are essential and play a significant ecological function (Chakraborty et al, 2023). Wetlands provide socio-economic benefits to society in addition to fishing and recreational activities (Islam et al, 2023). They also maintain the nutrient cycle in neighbouring agricultural regions, improve water quality, sequester carbon, and reduce floods in coastal areas (Balwan & Kour, 2021;Mitsch & Gosselink, 2015;Reddy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For integrated analysis of various datasets, ML provides advantageous computational and analytical methods (Marin et al, 2021). In addition to handling complex relationships between multisource input data and parameter estimation, ML algorithms can manage nonlinearity and complex training data (Islam et al, 2023). A wide range of algorithms has been developed and tested from parametric models such as maximum likelihood to nonparametric models such as support vector machine (SVM), artificial neural network (ANN), random forest (RF), and decision tree (DT) (Fu et al, 2022; Islam et al, 2023; Martínez Prentice et al, 2021).…”
Section: Introductionmentioning
confidence: 99%